Do environmental practices create value or legitimacy? Evidence from green accounting and environmental performance in Indonesia’s energy sector - Indira Geraldine Sugitan; Peter M. Kapojos (Riset Akuntansi dan Manajemen Pragmatis, 2026)
This study investigates whether environmental practices generate financial value or primarily serve as legitimacy mechanisms in environmentally sensitive industries. Drawing on legitimacy theory, it examines the impact of green accounting and environmental performance on firm financial performance in Indonesia’s energy sector. Using a sample of 19 listed energy companies over the 2021–2024 period (76 firm-year observations), this study employs multiple linear regression analysis. Green accounting is measured by environmental cost disclosure, environmental performance by PROPER ratings, and financial performance by Return on Assets (ROA). The findings reveal that green accounting has a negative and significant effect on financial performance, indicating that environmental expenditures impose short-term financial constraints. In contrast, environmental performance shows no significant impact, suggesting that compliance-based environmental ratings are not yet value-relevant for firms. However, both variables jointly affect financial performance. These results suggest that environmental practices in the energy sector are largely legitimacy-driven rather than value-driven. This study extends legitimacy theory by demonstrating that sustainability initiatives do not automatically translate into economic benefits, particularly in high-cost, regulation-intensive industries. The findings underscore the need for firms to shift from compliance-oriented environmental practices toward strategic sustainability integration to achieve long-term value creation.